2017
DOI: 10.1038/srep42764
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Protects against Palmitic Acid-Induced Apoptosis in Podocytes in vitro

Abstract: Autophagy is a highly conserved degradation process that is involved in the clearance of proteins and damaged organelles to maintain intracellular homeostasis and cell integrity. Type 2 diabetes is often accompanied by dyslipidemia with elevated levels of free fatty acids (FFAs). Podocytes, as an important component of the filtration barrier, are susceptible to lipid disorders. The loss of podocytes causes proteinuria, which is involved in the pathogenesis of diabetic nephropathy. In the present study, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 38 publications
6
52
0
Order By: Relevance
“…The conditionally immortalized murine podocyte clone 5 (MPC5) cell line was a kind gift from Dr. Ruan (The Centre for Nephrology, Royal Free and University College Medical School, London, United Kingdom); they were cultured as previously described [17, 18]. Briefly, cells were cultured and maintained on type I collagen-coated dishes in RPMI-1640 medium (Gibco, Karlsruhe, Germany) supplemented with 10% fetal bovine serum (Gibco), 100 U/mL penicillin, and 100 μg/mL streptomycin at two different temperatures in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditionally immortalized murine podocyte clone 5 (MPC5) cell line was a kind gift from Dr. Ruan (The Centre for Nephrology, Royal Free and University College Medical School, London, United Kingdom); they were cultured as previously described [17, 18]. Briefly, cells were cultured and maintained on type I collagen-coated dishes in RPMI-1640 medium (Gibco, Karlsruhe, Germany) supplemented with 10% fetal bovine serum (Gibco), 100 U/mL penicillin, and 100 μg/mL streptomycin at two different temperatures in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Podocyte apoptosis is one of the main risk factors causing podocyte loss [12, 16]. Our previous studies showed that palmitic acid (PA) can induce podocyte apoptosis [17, 18]. However, the precise mechanisms involved are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the conversion of LC3 from LC3‐I to LC3‐II is a characteristic of autophagy . As indicated in Figure E, LC3‐II/LC3‐I ratio was increased in A549 and A549/Taxol cells in a time‐dependent manner after exposure to BZML.…”
Section: Resultsmentioning
confidence: 82%
“…Most studies have reported that autophagy is an important factor for apoptosis resistance . Thus, our study mainly focused on clarifying the interaction between autophagy and MC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibiting lysosomal degradation with CQ induces p53-dependent cell death and prevents cancer in mouse models of lymphomagenesis. 99 In the pancreas of individuals with type 2 diabetes, cytokine interleukin-6 (IL-6) induces autophagy and protects pancreatic beta cells from apoptosis whereas CQ causes apoptosis and thereby elicits tissue damage. 94 In contrast, inhibition of autophagy by CQ may exacerbate diabetic neuropathy and impair neuronal function.…”
Section: Cq Regulates Tissue Responses To Metabolic and Inflammatory mentioning
confidence: 99%